2022
DOI: 10.3390/a15060188
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for Data-Driven Modelling from Harmonics in the Norwegian Grid

Abstract: With the advancing integration of fluctuating renewables, a more dynamic demand-side, and a grid running closer to its operational limits, future power system operators require new tools to anticipate unwanted events. Advances in machine learning and availability of data suggest great potential in using data-driven approaches, but these will only ever be as good as the data they are based on. To lay the ground-work for future data-driven modelling, we establish a baseline state by analysing the statistical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
0
0
Order By: Relevance
“…The impact of the increased strain on the power grid as a consequence of the increased electrification in the society were investigated in [2]. The study in [14], proposed a methodology to predict power failures by analyzing data from advanced electricity meters. The authors concluded that incipient power interruptions are easier to predict than earth failures and voltage dips.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the increased strain on the power grid as a consequence of the increased electrification in the society were investigated in [2]. The study in [14], proposed a methodology to predict power failures by analyzing data from advanced electricity meters. The authors concluded that incipient power interruptions are easier to predict than earth failures and voltage dips.…”
Section: Introductionmentioning
confidence: 99%